Endothelial cell ephrinB2-dependent activation of monocytes in arteriosclerosis - Braun, Jennifer; Hoffmann, Sabrina C.; Feldner, Anja; Ludwig, Thomas; Henning, Rob; Hecker, Markus; Korff, Thomas (Arteriosclerosis, thrombosis, and vascular biology, 2011)
Objective— - - The expression of ephrinB2 in endothelial cells delineates their arterial phenotype and is a prerequisite for the development of the embryonic vasculature. Whereas the role of ephrinB2 in the microcirculation has been studied extensively, its expression and function in adult arteries is hardly understood. - - Methods and Results— - - Our analyses showed that in mouse arteries, ephrinB2 is located on the luminal surface of endothelial cells and may physically interact with monocyte EphB receptors. Moreover, transdifferentiation of human monocytes into macrophages was associated with an increase in EphB2 expression, and exposing monocytes to immobilized ephrinB2 resulted in phosphorylation of the receptor followed by an increased expression of proinflammatory chemokines such as interleukin-8 and monocyte chemotactic protein-1/CCL2. Relating to the (patho)physiological relevance of these findings, immunofluorescence analyses revealed that ephrinB2 is most abundantly expressed in endothelial cells at arteriosclerosis predilection sites of the mouse aorta. Subsequent analyses indicated that monocyte adhesion to aortic segments abundantly expressing ephrinB2 is strongly enhanced and that endothelial cell ephrinB2 forward signaling is sufficient to upregulate cytokine expression in monocytes. - - Conclusion— - - These observations suggest a hitherto unknown link between vascular ephrinB2 expression and the proinflammatory activation of monocytes that may contribute to the pathogenesis of arteriosclerosis.